Lobectomy: no port at all? - Ren, Yanping; Jiao, Yuxin; Zheng, Xiangpeng (Annals of Translational Medicine, 2017)
Over decades of development, surgical procedures in stage I non-small cell lung cancer (NSCLC) have been advanced from open thoracotomy to video-assisted minimally invasive thoracoscopic surgery (VATS). Lobectomy (with preference of VATS technique) remains the standard of care for stage I NSCLC (1). The unstopping advances in surgical devices and techniques have contributed to the VATS transition from the conventional multiportal approach to uniportal approach, which has demonstrated advantages in safety and preservation of patient’s quality of life over the former (2). Curiously, is that possible to perform lobectomy with no port at all, or to rephrase the question, is a noninvasive procedure reasonable and available for definitive treatment of this malignancy with outcomes same to or even better than surgery?